SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMBERIAN BEASISWA “PROGRAM JONT DEGREE” UNIVERSITAS BHAYANGKARA SURABAYA MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Alek Siswanto; Syariful Alim (NJCA (Nusantara Journal of Computers and Its Applications), 2018)
Grant scholarships to students are conducted by the University based on the achievements achieved. Since the last few years Bhayangkara University has run a Joint Degree Program scholarship in cooperation with Thailand, India, and plans to continue to the Netherlands. In scholarship grants, the Universityoften finds it difficult to determine the scholarship recipients, so it is found that scholarships are not accurate due to the manual system for the awarding of scholarships. The decision support system is an information system aimed at assisting the University in solving the problem of awarding Joint Degree Program scholarship. One method that can be used in decision support systems is Analitycal Hierarchy Process (AHP). The Analytical Hierarchy Process (AHP) method takes into account the extent of validity to the extent of inconsistency tolerance of the various criteria and alternatives chosen by the decision maker. In this research, the data used is UBHARA student data 3 last generation. The criteria used are GPA, TOEFL score, TPA Test Score, and Value of Communication Skill Test. From the results of experiments carried out the results of manual calculations of the application and manual calculations from the Institute of Cooperation get a presentation 100% equation in determining scholarship recipients. So as to produce the ranking of students, two students with the highest score in each department that will get a Joint Degree Program scholarship.Keywords: Scholarship, Student, Analytical Hierarchy Process (AHP), Decision Support System.